Effects of plant architecture and prey distribution on the foraging efficiency and behavior of the predatory mite Phytoseiulus persimilis (Acari:phytoseiidae) - Gontijo, Lessando Moreira (Kansas State University, 2008)
The study of how extrinsic factors affect the foraging efficiency and behavior of predaceous arthropods like Phytoseiulus persimilis is important to understand their various processes of acquiring prey, mates, refuges, oviposition sites, and overcoming obstacles posed by the environment. Many intrinsic and extrinsic factors affect predator foraging efficiency and behavior. One of the most influential extrinsic factors may be the host plant on which herbivorous prey are found. Recent studies suggest that plant architecture plays an important role in tritrophic interactions. In this work, I studied the effects of cucumber plant architecture and prey distribution on the foraging efficiency (prey-finding time and prey-consumption rate) and behavior (time allocated between moving, resting and feeding) of P. persimilis. Plant architecture represented differences in leaf number and size; however, all plants had the same total surface area. Plants with 6 small leaves (ca. 82.98 square cm each) were considered as complex architecture, whereas plants with only 2 large leaves (ca. 240.60 square cm each) were considered as simple. The prey distributions were: prey patch on a single basal leaf (closest leaf to the soil) and prey patch on all leaves. The foraging efficiency was assessed by measuring prey-finding time and prey-consumption rate, whereas the behavior was assessed by conducting observational studies on specific foraging activities. When placed either on the top or at the base of the plant P. persimilis encountered prey more rapidly (interval 0-30 minute) on complex and simple plants with prey patches distributed on all leaves. Differences in prey density (number of prey per leaf) had no effect on the prey-finding time of P. persimilis. The predator consumed more eggs on complex plants with prey patches distributed on all leaves. Phytoseiulus perismilis tended to find prey patches more quickly as well as consume more eggs on leaves close to its release point. Furthermore, the predator was observed to lay more eggs on leaves where it had consumed higher number of prey eggs. The dimensions of individual parts of the plant e.g., stem, petiole and leaf, affected the time allocated by P. persimilis between searching, resting and feeding. The predatory mite spent more time foraging on the stems and petioles of the simple plants whereas on complex plants it spent more time foraging on the leaves.
Keywords: Plant architecture; Prey distribution; Phytoseiulus persimilis; Foraging efficiency; Foraging behavior; Agriculture, Agronomy (0285); Biology, Ecology (0329); Biology, Entomology (0353)